Implementasi Solar Shelter untuk Menunjang Sistem Energi Terbarukan yang Berkelanjutan di Pulau Gili Iyang, Kabupaten Sumenep - Mubarok, Muhammad Syahril; Apsari, Retna; Uta Nugraha, Yoga; Amelia Effendi, Yutika; Jamilatul Awalin, Lilik; Purbandini, Purbandini; Sofiah, Amila; Rantini, Dwi; Fahmiyah, Indah (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2025)
Limitations in electricity access and reliability remains a critical challenge for small islands and remote areas in Indonesia, constraining socio-economic development and sustainable tourism growth. This community engagement program aimed to design and implement a solar shelter system to support renewable energy utilization in Gili Iyang Island, Sumenep, widely recognized as an “oxygen island” and emerging health tourism destination. The program adopted a participatory approach involving local youth organizations (Karang Taruna) and the Kelompok Sadar Wisata (Pokdarwis) through needs assessment, system design, installation, testing, and technical training. The implemented off-grid photovoltaic system consists of a 100 Wp solar panel, a 24 V 20 A solar charge controller, a 12 V 50 Ah VRLA battery, and a 1000 W pure sine wave inverter supplying 220 V AC loads. Field testing demonstrated that the system reliably powered an automatic coconut irrigation pump and multiple electronic charging devices under typical operating conditions. Beyond technical performance, the program enhanced local capacity in basic solar energy operation and maintenance while strengthening the island’s image as a sustainable ecotourism destination. The initiative directly contributes to SDG 7 (Affordable and Clean Energy) and supports long-term renewable energy adoption in small island contexts.